AFIKSASI BAHASA TERNATE - Nasrullah La Madi; Rafli Marwan (Universitas Khairun, 2022)
Ternate language is currently predicted to be threatened with extinction. One of the factors is the need for cross-ethnic communication using Bahasa Melayu Ternate (a lingua franca used among cross-ethnic communication in North Maluku)Â that resulted in a decline in the number of Ternate speakers. Ternate language identity vocabulary began to be forgotten and replaced it with Malayu Ternateâ€™s vocabulary. Therefore, as a form of inventory, this morphological research in the field of affixation is the hope of awakening the vocabulary of the Ternate language identity that has been forgotten or abandoned. The purpose of this study was to find and analyze the affixation of the Ternate language. This research method uses descriptive qualitative. Sources of data obtained from informants and supporting data from previous research, books, and so on. The research location was in Dufa-Dufa village, North Ternate. The data collection techniques through observation, interviews, and recordings. The data analysis technique is through the stages of data reduction, presentation, and verification. The results showed that Ternate language affixation consisted of (1) prefixation, (2) infixation, (3) suffixation, and (4) confixation. Ternate language prefixes such as ma-, si-, and ngu-. Ternate language infixation such as -ho- and -ro-. Ternate language suffixes such as -u and -i. Ternate language conventions such as siâ€“i.